Administration law - Ramachandran, V.G. (Lucknow, 1984)
This book has in five chapters covered Introductory: Origin and Deve lopment of Administrative Law, Administrative Process, Administrative Justice, Administrative Procedure and Remedies, and Administrative Tribu nals. A study of the Tribunals in India has been presented as also a Table of the Tribunals under the Central Acts (1850-1968). Appropriate citations from the Report of the Committee on Minister's powers, Franks Committee Report and the Attorney-General's Committee Report have been fully given in relevant pages with a view to help the reader in having a full picture of the development of Administrative Law in England and America. This is necessary as the growth of Administrative Law in India is modelled mostly on the systems prevalent in those countries. The ramifications in Administrative Law are manifold. The author has tried to help the reader to get at what he wants by reference not only to the buxom synopsis at the beginning of each chapter but also by reference to the copious Index furnished at the end of this treatise.
Keywords: Administration law